Concentration and smash accuracy: A correlational study - Eval Edmizal; Eri Barlian; Alnedral Alnedral; Wilda Welis; Donie Donie (Global Econedu, 2023)
The accuracy of the smash in the badminton game is very necessary so that the smash punch is difficult to return by the opponent. Accurate smash punches will help the player to win the match. This study aims to see the relationship between concentration and smash accuracy. This study used the correlational method by conducting concentration tests and smash accuracy to 20 coaching department students who were taking badminton courses. Concentration tests and smash accuracy tests were used to collect data on this study. The results showed that there was a significant relationship between concentration and smash accuracy in badminton. The coaches should provide concentration training to their players so that the players' smash accuracy can be more optimal.